ECONOMIC EVALUATION OF POWER WAVES AT THE BEACH TEGAL - Soebyakto Soebyakto (Universitas Gadjah Mada, 2016)
Observations of electric power of the waves hitting beach Tegal is obtained by finding the value of the speed, frequency and height of the waves on the beach Tegal. The average value of the wave velocity of 0.15 m/s, the average frequency of 0.17 Hz and a maximum height of 0.6 m on average. This data is still too low to generate electrical power from the mechanical power of the waves. We are still conducting research to increase the speed and height of the waves with a method of